Peran Manajemen Organisasi Dalam Kemajuan Pendidikan - Tanzila Bahar; Nazry Nasyifa; Afrohul Fadhillah; Ahmad Mukhlasin (Lembaga Pengembangan Kinerja Dosen, 2024)
Management of educational organizations requires a planned and comprehensive strategy to overcome challenges such as resistance to change, limited technology infrastructure, need for training, data security, digital divide and cultural challenges. Collaboration is needed to effectively utilize digital technology in education. This research aims to explore the role of organizational management in educational advancement. The research method is based on the previously described theories of management and leadership, as well as the results of previous research. The results show that good organizational management can transform education, focusing on effective resource management, consistent evaluation, professional development and increased employee motivation. Keywords: , ,